Robustness, sensitivity and reproducibility of eDNA metabarcoding as an environmental biomonitoring tool in coastal salmon aquaculture – An inter-laboratory study - Verena Dully (Elsevier, 2021)
Environmental DNA metabarcoding of benthic bacterial communities emerged as a very powerful technology to assess environmental disturbance effects of coastal salmon aquaculture. A prerequisite for the implementation of this approach into compliance monitoring regulations is its robustness and reproducibility of obtained results. In the framework of regular compliance monitoring of a Scottish salmon farm, we therefore collected sediment samples along a transect from the salmon cages to reference sites in duplicates (biological replicates). Aliquots of both biological replicate samples were then processed by two different laboratories using independently the same eDNA metabarcoding protocol (technical replicates). Measures of alpha diversity and beta diversity, as well as taxonomic profiles of benthic bacterial communities were highly congruent among technical replicates, which even showed less variations then the biological replicates that were processed within each laboratory. Both technical replicate datasets identified the same bacterial indicator taxon groups and ASVs that are characteristic for the environmental quality (EQ) categories to which each of the samples was assigned based on traditional macroinvertebrate biomonitoring of the same samples. In a supervised machine learning (SML) approach, we could classify all individual samples from one technical replicate dataset into the correct EQ category using all samples of the other technical replicate dataset as a training dataset for the SML algorithm. We conclude that eDNA metabarcoding is sufficiently robust that different laboratories come to the same conclusions regarding officially regulated action criteria for environmental impact assessments in salmon aquaculture.